Faktor Penglibatan Belia Muslim Malaysia dengan Terorisme: Analisis Perspektif PDRM dan Panel Pemulihan Deradikalisasi: Factors of Malaysian Muslim Youth Involvement in Terrorism: An Analysis on the Perspectives of PDRM and Deradicalization Panel - Che Nordin, Mohd Khairul Naim; Mhd Nazer, Muhamad Syafriz (Jurnal Usuluddin, 2020)
This article examines the involvement factors of Malaysian Muslim youth with terrorism. Various theories have been put forward by researchers to identify these factors in general but studies conducted show that these factors differ from one country to another. Thus, to obtain direct data on the factors of youth terrorist involvement in Malaysia, this study conducted a semi-structured interview with two parties which directly involved in the activities of prevention, control and enforcement of terrorism namely the Anti-Terrorism Unit (E8) Special Branch, Royal Malaysia Police and members of terrorist deradicalization programme, Ministry of Home Affairs. E8 Unit plays a role in identifying and arresting terrorist suspects while members of the deradicalization programme interact directly with the offenders and then carry out the deradicalization process towards them. In addition to this data, the study also conducted interviews with academicians and one family member’s of the offender arrested under the Prevention of Terrorism Act (POTA). The results of the interviews were then formulated analytically based on documented library references. The study found that there are five major factors that attract youth into terrorism, namely psychological and personality, religious knowledge, social media, ideology and conflict in Muslim countries. Each of these factors serves as a catalyst for the youth to engage in terrorism. In summary, the identification of these factors is crucial in the efforts of all parties to prevent terrorism among the Malaysian youth.